"Embodied Technical Change and Productivity in the United States 1929-1958."–A Comment - Denison, Edward F. (The Review of Economics and Statistics, 1968)
An article by Michael D. Intriligator entitled Embodied Technical Change and Productivity in the United States 1929-1958 appeared in the February 1965 issue of this REVIEW. To judge the importance of embodied and disembodied technical progress, Intriligator computed 40 correlations of gross national product, excluding GNP originating in government and housing, with capital and labor input. All 40 regressions resulted from combining four alternative measures of labor input, three of them mine, with five alternative capital series based on different assumptions about embodiment, and two methods of handling trend. To match Intriligator's GNP measure, labor input must exclude all general government employees. The data Intriligator actually used, however, include all government employment: civilian, military, and work relief. The period covered, 19291958, spanned the Great Depression, World War II, and the Korean War, periods in which the share of government employment was fluctuating violently, as well as a postwar period in which most of the employment increase was devoted to government. Intriligator's results consequently seem to have no apparent meaning. An interesting feature of the article is that all 40 regressions Intriligator computed have high correlation coefficients despite his use of irrelevant data; only one is below 0.95 and most are above 0.98. This may give further reason for skepticism about the utility of inferring causation -in this case, degree of embodiment-from minor differences in the goodness of fit of time series.